Graphical design for stability of linear active disturbance rejection control to first order time delay plants. (27th November 2012) - Yang, Ruiguang; Sun, Mingwei; Chen, Zengqiang
In this paper, a Linear Active Disturbance Rejection Control (LADRC) scheme is presented for the uncertain first order delay time plant. The stable boundary is obtained, which make the tuning process very easy. The controller can be applied to a plant with large time delay. The uncertainty of the system is characterised by the Kharitonov theorem and the gain–phase margin tester approach, combined with the D–partition method, is utilised to determine specific performance boundaries. The analysis is conducted graphically and the feasible regions are explicitly shown in the parameter plane. Numerical simulation is provided to demonstrate the effectiveness of the proposed controller.